Evaluation of IL-6 and IgE Levels in Iraqi Patients with Chronic Spontaneous Urticaria (CSU) in Baghdad, Iraq. - Ahmed, Riyam; Abdullah Hussein, Talib; Almas Brakhas, Suaad (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
A skin condition known as chronic spontaneous urticaria (CSU), which lacks an obvious triggering factor, is characterized by recurrent transient wheals, angioedema, or both for longer than six weeks. the current study was focused to study compared and diagnosis CSU by using heamatological and immunological parameters as (White blood cell count, eosinophils (EO), IL-6 and Total-IgE, in Chronic Urticaria patients were Clinically diagnosed by dermatologists in Specialized Center of Allergy in Baghdad/Al-Rusafa with age ranged between (11-60), as well as a control group included 40 with age ranged between (11-60). The results of demographic and clinical characteristics displayed the rate of female patients was higher than male which represented by 56.3 and 43.8% respectively. The results showed there was highly significant differences between the patients and the control in WBC , Total-IgE ,IL-6 the results showed EO was higher than control but no significant difference at p ≤ 0.05. The eosinophils percentage was high in age 51-60 and 21-30 year while those with age 41-50 and 51-60 year had highest, Total-IgE level 211.7 ±38.96 IU/ml, 211.69 ±38.71IU/ml respectively but IL-6 level was highest 26.4 ±1.77 pg/ml in patients with age group 21-30 year. WBC count in age 41-50 and 51-60 year showed highest count 9.2 ±1.34 cell/cm³blood, 9.3±1.21 cell/cm³blood respectively. In same time the values of parameters were various between patients without treatment and in patients who undergoes into treatment, Finally The ROC showed the IL-6 and Total-IgE were discriminated as accurate biomarkers for CSU.